Hybrid heating installations - Marian Sobiech (Biuletyn Wojskowej Akademii Technicznej, 2017)
The article presents important considerations related to the use of renewable energy installations in modern buildings for various purposes. The essence of the matter is the question of an innovative technical solution for heating installations and preparation of hot water in moderate climate conditions, in order to obtain the effect of the lowest cost of the maintenance and operation of the building in the heating season. Keywords: construction, buildings heating, renewable energy, hybrid installations